Sociodemographic Factors Associated With Oral Health-Related Quality Of Life Among Elderly Population - Yufitri Mayasari; Mutiara Rina Rahmawati Ruslan; Sarah Mersil; Elin Hertiana; Tirani Bina Viraningtyas (Journal Research of Social Science, Economics, and Management, 2023)
The aim of the study was to analyze sociodemographic factors associated with oral health-related quality of life among elderly population. Methods: a cross-sectional study was undertaken in 20-23 February 2022 with 75 elderly people aged 60 years and older. This sample size was representative of the geriatric population living at home in the RW 02, Kelurahan Sukahati, Kecamatan Cibinong, Kabupaten Bogor. Participants were interviewed at home by trained interviewers using a 15-item questionnaire that included socio-demographic indicators (gender and age). Participants' OHRQoL were evaluated using a validated Indonesian version of GOHAI. The questionnaire consisted of 12 questions, with answers ranging from 1 to 5. GOHAI evaluates three aspects: (A) Physical functions such as speaking, eating and swallowing. (B) Dissatisfaction with appearance and psychosocial effects, including contact with others, self-esteem for oral health, and concerns about appearance. (C) Pain or discomfort, including taking medication to relieve pain. Results: a total of 75 participants completed the questionnaire. Most of the participants were between 60-69 years old (52%). The study population included 33 men (44%) and 42 women (56%). Most of the participants reported a poor OHRQoL score (GOHAI ? 56). There was significantly associated between age and gender with GOHAI category (p = 0.026, CI 95%; p = 0.000, CI 95%). Conclusion: most of respondents reported a poor oral health related quality of life. Sociodemographic factors (age and gender) associated with oral health related quality of life in elderly people.